Genomic characterisation of endangered Landim pigs reveals distinctive features and immune-related selection - Teixeira, Fábio; Sá, Pedro; Santos, Dulce; Garrine, Carmen; Zimba, Rosa; Augusto, Laurinda; Varela-Martínez, Endika; Chiaia, Hermenegildo; Sebastino, Kiala; Cordeiro, José M.; Leitão, Alexandre; Gama, Luís T.; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe Landim pigs of Mozambique are an important local breed, reared by smallscale farmers in extensive systems, predominantly sustained on leftover food. These pigs serve as a cornerstone of the economic stability of these communities. However, their existence is currently threatened by uncontrolled crossbreeding with commercial pig breeds. Preserving these local pigs is also crucial, given their role as a source of genetic diversity.MethodsWhole-genome resequencing of samples derived from six Landim pigs,was conducted, to characterise their genetic makeup and establishing their relationship with pig breeds worldwide.ResultsOur findings suggest that Landim pigs are more closely related to Angolan pigs, although recent introgression from European cosmopolitan breeds has occurred.DiscussionResults show that Landim pigs display a unique genetic signature, with positive selection detected in variants of genes acting within the neuroimmune axis, which is fundamental for survival and immune response.